Carbon Black and Lignin Hybrid Filler in Designing NR Based Cushion Gum Composite Formulation - Santi Puspitasari; Adi Cifriadi (Institute for Research and Community Services, Institut Teknologi Bandung, 2022)
Lignin has high potential to be used as rubber cushion gum compound ingredient due to its unique properties. Cushion gum is an adhesive used to bind a new tread to the surface of used tires in a retread tire factory. An experiment was carried out to evaluate the performance of hybrid filler consisting of carbon black and lignin in affecting the physical and mechanical properties of natural rubber (NR) based cushion gum composite. The composition of carbon black/lignin was arranged at 40/10 phr and 35/15 phr. Carbon black grade N220, N330, and N550 were used in this research. Meanwhile, the lignin was specifically in the form of sodium lignosulfonate. The cushion gum compound was also formulated with the addition of pine tar oil as bio-based plasticizer. Commercial cushion gum was used as a comparison. The result showed that the hybrid filled NR cushion gum composite with N330/lignin at 40/10 (coded as SP2) was the most appropriate formula. Compared to commercial cushion gum, the SP2 hybrid filled cushion gum had comparable or even better processability and mechanical properties, attributed to high crosslink density. The excellent adhesive strength of the SP2 NR cushion gum composite was due to the presence of high content of the phenolic functional group in lignin and pine tar oil.